Validity Evidence of the Reading Screening Test for Portuguese First Graders - Silva, Ana Filipa; Marques, Cátia; Sucena, Ana (Frontiers in Education, 2020)
This study aims to present validity evidence for the Reading Screening Test (TRL-Teste de Rastreio de Leitura) that assesses word and pseudoword reading. Participants were 94 Portuguese first graders (49 girls and 45 boys), assessed with the TRL and criterion measures – ALEPE subscales to assess words, pseudowords reading and Rapid Automatized Naming. Results from confirmatory factor analyses indicated that a two-factor measurement model yielded a good fit to the data. Favorable estimates of internal consistency reliability were obtained. Correlation coefficient results suggested that the measure was positively and statistically associated with another measure of reading assessment. These results revealed adequate evidence based on internal structure and evidence based on the relationship to other variables for the assessment of word reading accuracy among Portuguese first graders.